(untitled) (CIPEEX, 2024)
PUBLIC MANAGEMENT REPRESENTS A FIELD OF GREAT OPPORTUNITIES AND GREAT OBSTACLES, HOWEVER, WITH INNOVATION, ONE CAN COUNT ON A SOLUTION TO ALLEVIATE DIFFICULTIES AND MAKE MANAGEMENT RUN MORE EFFECTIVELY AND OBJECTIVELY. THE MAIN FOCUS OF THIS MANAGEMENT IS TO WALK SIDE BY SIDE WITH THE GREAT CHANGES THAT THE MARKET DEMONSTRATES EVERY DAY, ALWAYS AIMING AT IMPROVEMENTS WITH THE RESOURCES THAT ARE OFFERED TO IT. AMONG THE MAIN DIFFICULTIES FACED ARE: LACK OF COMPETENT AND GRADUATED PEOPLE TAKING IMPORTANT POSITIONS, INCORRECTLY DISTRIBUTED FUNDS AND EXCESSIVE SPENDING THAT COULD BE DESTINED TO OTHER AREAS WITH GREATER NEED. IN INNOVATION THERE ARE FACTORS THAT ENABLE THE CONTRIBUTION TO A CREATIVE ENVIRONMENT, FACTORS SUCH AS: BROAD MANAGEMENT PROCESSES, AUTONOMY AND OPPORTUNITIES FOR AGILITY IN DECISION MAKING. THE OBJECTIVE OF THE RESEARCH IS TO EVALUATE THE WAY IN WHICH INNOVATION IN PUBLIC MANAGEMENT PERFORMS THE OPTIMIZATION OF RESOURCES THROUGH INNOVATIVE IDEAS. AS A RESEARCH METHOD, QUALITATIVE DATA WAS USED IN ARTICLES REFERRING TO THE AREA OF MANAGEMENT AND INNOVATION, IN WHICH THEY COVER THE YEARS 2018 TO 2022, BEING SEARCHES IN DATABASES SUCH AS SCIELO, CAPES JOURNALS, SPELL AND GOOGLE SCHOLAR. AMONG THE RESULTS, IT IS NOTED THAT SINCE THE 90S INNOVATION HAS BEEN CONTRIBUTING WITH MAJOR CHANGES IN MANAGEMENT, THUS IMPROVING THE DEVELOPMENT OF GOVERNMENT ACTIONS AND BECOMING A MAJOR RESPONSIBLE FOR ITS MECHANISM OF PROBLEM SOLVING. IT IS THUS SEEN, MORE CLEARLY, AS PUBLIC MANAGEMENT TOGETHER WITH INNOVATION, HAS BEEN GAINING PROMINENCE INCREASINGLY IN THE 21ST CENTURY, WHERE THE BEST INNOVATION RESOURCES ARE REACHING A PEAK IN STATE ORGANIZATIONS, THIS IN ORDER TO ENSURE THAT THE PRINCIPLES OF EFFICIENCY AND QUALITY IN MANAGEMENT ARE MET, ALWAYS AIMING AT THE IMPROVEMENTS THAT CAN BE MADE AT THAT TIME.&NBSP; DUE TO THE INFORMATION MENTIONED, INNOVATION IN THE PUBLIC SECTOR HAS BEEN AN ENVIRONMENT OF VARIOUS POSSIBILITIES WITHIN THE ORGANIZATIONAL ENVIRONMENT WHEN IN FACT IT CAN GENERATE AND CONTROL THESE POSITIVE CHANGES IN PUBLIC ADMINISTRATION, DIRECTLY COVERING THE INTERNAL ORGANIZATION AND IMPROVING ALL PROCESSES FROM PLANNING, CONTROL, EXECUTION OF SERVICES, APPROACHES AND IMPLEMENTATION OF TOOLS, THIS IN ORDER TO INCREASE REVOLUTIONARY TYPOLOGIES THAT PROMOTE BENEFITS TO SOCIETY, SERVICE, REFLECTING POSITIVELY IN THE STATE. INNOVATION IN PUBLIC MANAGEMENT MAKES SERVICE FAST, WHICH TODAY IS A SURPRISE TO MANY, WITHOUT LEAVING ASIDE EFFICIENCY AND RESULTS ARE VISIBLE AND NOTICEABLE, DUE TO ITS ABILITY TO MITIGATE OBSTACLES, IMPROVE THE RESOURCES OFFERED, AGILITY IN PROCESSES. ONE CAN ALSO HIGHLIGHT THE FACT THAT THIS MANAGEMENT NEEDS INNOVATION AT ALL TIMES.